The Potential of Psidium Guajava as an Antidiabetic a Review - Mohammad Zainul Ma'arif; Alfan Ridha; Yuniars Renowening; Titik Dwi Noviati; Himmatunnisak Mahmudah (Jurnal EduHealth, 2023)
Psidium guava is known as a fruit that contains many bioactive compounds such as polyphenols, flavonoids, and heteropolysaccharides. This review presents the results of the latest research on the effect of guava fruit on type 2 diabetes mellitus. It is proven that guava fruit can act as an antihyperglycemic therapy through mechanisms that include repairing pancreatic cells, increasing insulin sensitivity, inhibiting α-glucosidase, and inhibiting SGLT1 and GLUT2 transporters. These results prove the potential of guava fruit as a functional food for glycemic control in patients with type 2 diabetes mellitus.